Protective Efficacy of an Orf Virus-Vector Encoding the Hemagglutinin and the Nucleoprotein of Influenza A Virus in Swine - Joshi, Lok R.; Knudsen, David; Piñeyro, Pablo; Dhakal, Santosh; Renukaradhya, Gourapura J.; Diel, Diego G. (Frontiers in Immunology, 2021)
Swine influenza is a highly contagious respiratory disease of pigs caused by influenza A viruses (IAV-S). IAV-S causes significant economic losses to the swine industry and poses challenges to public health given its zoonotic potential. Thus effective IAV-S vaccines are needed and highly desirable and would benefit both animal and human health. Here, we developed two recombinant orf viruses, expressing the hemagglutinin (HA) gene (OV-HA) or both the HA and the nucleoprotein (NP) genes of IAV-S (OV-HA-NP). The immunogenicity and protective efficacy of these two recombinant viruses were evaluated in pigs. Both OV-HA and OV-HA-NP recombinants elicited robust virus neutralizing antibody response in pigs, with higher levels of neutralizing antibodies (NA) being detected in OV-HA-NP-immunized animals pre-challenge infection. Notably, aAlthough both recombinant viruses elicited IAV-S-specific T-cell responses, the frequency of IAV-S-specific proliferating CD8+ T cells upon re-stimulation was higher in OV-HA-NP-immunized animals than in the OV-HA group. Importantly, IgG1/IgG2 isotype ELISAs revealed that immunization with OV-HA induced Th2-biased immune responses, whereas immunization with OV-HA-NP virus resulted in a Th1-biased immune response. While pigs immunized with either OV-HA or OV-HA-NP were protected when compared to non-immunized controls, immunization with OV-HA-NP resulted in higher incremental protective efficacyprotection against challenge infection as evidenced by a reduced secondary antibody response (NA and HI antibodies) following IAV-S challenge and reduced virus shedding in nasal secretions (lower viral RNA loads and frequency of animals shedding viral RNA and infectious virus), when compared to animals in the OV-HA group and reduced viral load in the lung. Interestingly, broader cross neutralization activity was also observed in serum of OV-HA-NP-immunized animals against a panel of contemporary IAV-S isolates representing the major genetic clades circulating in swine. This study demonstrates the potential of ORFV-based vector for control of swine influenza virus in swine.